Legumes and common beans in sustainable diets: nutritional quality, environmental benefits, spread and use in food preparations - Lisciani, Silvia; Marconi, Stefania; Le Donne, Cinzia; Camilli, Emanuela; Aguzzi, Altero; Gabrielli, Paolo; Gambelli, Loretta; Kunert, Karl; Marais, Diana; Vorster, Barend Juan; Alvarado-Ramos, Katherine; Reboul, Emmanuelle; et al. (Frontiers in Nutrition, 2024)
In recent decades, scarcity of available resources, population growth and the widening in the consumption of processed foods and of animal origin have made the current food system unsustainable. High-income countries have shifted towards food consumption patterns which is causing an increasingly process of environmental degradation and depletion of natural resources, with the increased incidence of malnutrition due to excess (obesity and non-communicable disease) and due to chronic food deprivation. An urgent challenge is, therefore, to move towards more healthy and sustainable eating choices and reorientating food production and distribution to obtain a human and planetary health benefit. In this regard, grain legumes represent a less expensive source of nutrients for low-income countries, and a sustainable healthier option than animal-based proteins in developed countries. Although grain legumes are the basis of many traditional dishes worldwide, and in recent years they have also been used in the formulation of new food products, their consumption is still scarce. Common beans, which are among the most consumed pulses worldwide, have been the focus of many studies to boost their nutritional properties, to find strategies to facilitate cultivation under biotic/abiotic stress, to increase yield, reduce antinutrients contents and rise the micronutrient level. The versatility of beans could be the key for the increase of their consumption, as it allows to include them in a vast range of food preparations, to create new formulations and to reinvent traditional legume-based recipes with optimal nutritional healthy characteristics.